(3cTa GdXdGe Yf hLhg TQGFY GdESdGes - (3eMSf Hf eQJVi Hf bGSe, J (B1238 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3hCeG CMcGegG GdJcdjajI hGdhVYjI aj GdLedI GdGSJZQGbjI(B...s
(3BNQgG (B:s
(3aYdi GdeTghQ Ef hGab QGj GdeCehe EeGeg (B... (3hYdi eNJGQfG jHbi Ydi GdEJeGe(B. (3JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B22s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B22s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis